Interleukin-27 in T Cell Immunity - Iwasaki, Yukiko (Int J Mol Sci, 2015)
Interleukin (IL)-27, a member of IL-12/IL-23 heterodimeric family of cytokines, has pleiotropic properties that can enhance or limit immune responses. IL-27 acts on various cell types, including T cells, B cells, macrophages, dendritic cells, natural killer (NK) cells and non-hematopoietic cells. Intensive studies have been conducted especially on T cells, revealing that various subsets of T cells respond uniquely to IL-27. IL-27 induces expansion of Th1 cells by activating signal transducer and activator of transcription (STAT) 1-mediated T-bet signaling pathway. On the other hand, IL-27 suppresses immune responses through inhibition of the development of T helper (Th) 17 cells and induction of IL-10 production in a STAT1- and STAT3-dependent manner. IL-27 is a potentially promising cytokine for therapeutic approaches on various human diseases. Here, we provide an overview of the biology of IL-27 related to T cell subsets, its structure, and production mechanism.